Physical Fitness and Quality of Life Analysis of Junior High School - Firjatulloh Nafiah; Nuryadi; Agus Gumilar (Universitas Negeri Semarang, 2026)
Adolescents tend to engage more in passive activities than in physical activities, which leads to decreased physical fitness and quality of life. This study aims to analyze the level of physical fitness, quality of life, and distribution of Body Mass Index (BMI) in Pelita Fajar Junior High School students. The study used a quantitative descriptive method with a total sampling technique involving 47 students. Physical fitness measurement uses the Indonesian Physical Fitness Test (TKJI) aged 13–15 years, which includes running 50 meters, hanging from the elbows, lying down, jumping upright, and running 800/1000 meters. Quality of life was measured using a questionnaire that included four domains, namely physical, psychological, social, and environmental. The results showed that the physical fitness level of students was dominated by medium (38.3%) and low (29.8%) categories, and there was no very good category. The quality of life of students is mostly in the moderate category (53.2%). Correlation analysis showed a strong relationship between quality of life domains with correlation coefficient values ranging from r = 0.653 to 0.714. BMI distribution is dominated by underweight (40.4%) and normal (38.3%) categories. Students with normal BMI had a higher median physical fitness (≈14) than the underweight (≈13), overweight (≈12), and obesity (≈12.5) categories. These findings show that BMI balance plays a role in supporting physical fitness as well as being related to students' quality of life.